Caravaggio and the Baroque - Caraggio, Michelangelo Merisi da 1573-1610; Hribar, Mariano Nicora (Masterpeices of Italian Art, 1990)
Presents key masterpeices of artistits during the Baroque period like Carravaggio Conegio, lotto Parmigriamino, Tintoretto, Sansoriano, Palladio, Bernini and Benomini.